ANALISIS PELANGGARAN PROGRAM OBSESIBERDASARKAN PEDOMAN PERILAKU PENYIARAN DAN STANDAR PROGRAM SIARAN - Rizki Hoirul Anam; Qoni’ah Nur Wijayani (Jurnal Media Akademik (JMA), 2024)
Television is one of the most popular mass communication media in Indonesia. However, as time progresses, the presence of television is starting to be liked by many people because now there are many digital media that are more practical to use. GTV is one of the private television stations in Indonesia which has a variety of entertainment and news programs. The presence of TV program violations can have a significant impact on the broadcast and image of a television station. TV programs have a big influence on society, especially children and teenagers, so it is important to understand the consequences of violating TV programs which can damage social, moral and cultural values. One of the programs from GTV is “Obsesi”. “Obsesi” is an infotainment television program (entertainment information), every program broadcast on television must comply with the regulations stated in the Broadcasting Code of Conduct and Broadcast Program Standards (P3SPS). The Indonesian Broadcasting Commission or KPI for short issued P3SPS regulations which aim to limit broadcast programs so that they do not violate existing norms. The results of research and existing data show that the Obsession program violated P3SPS regulations. On January 20 2020 at 09.28 WIB, there was a scene of communication with astral beings through the medium of a woman who told the story of Ashanty who was suspected of receiving black magic/witchcraft